Comparison of Nutritional Quality and Organoleptic of Dadih (Minangkabau Traditional Yogurt) of Cow Milk and Soy Milk as Functional Food Probiotics (Global Journal of Medical Research, 2019)
Functional food was defined as foods that are nutritious and also have a positive influence on health. One of the functional foods which was a typical traditional food of Minangkabau was Dadih. Dadih was a nutritious food for the health of the human body. One of the properties of Dadih was to reduce blood cholesterol because it contains Lactic Acid Bacteria (LAB) which are potential as probiotics. Dadih can be made from cow's milk or soy milk but must be added with skim milk so that the total solid is equal to buffalo milk Dadih. The purpose of this research was to determine protein content, fat, yield, organoleptic properties of Dadih. This research was an experimental study with two treatments and two replications and analyzed using a 5% T-test. The results obtained from this study were significant differences in protein, fat, and color between cow milk Dadih and soybean. Whereas from the organoleptic test results showed 60% of panelists like pure soybean Dadih compared with cow milk.
Keywords: functional food; dadih; cow#x2019; s milk; soybean milk; organoleptic